2019
DOI: 10.3390/molecules24193507
|View full text |Cite
|
Sign up to set email alerts
|

Promutagenicity of 8-Chloroguanine, A Major Inflammation-Induced Halogenated DNA Lesion

Abstract: Chronic inflammation is closely associated with cancer development. One possible mechanism for inflammation-induced carcinogenesis is DNA damage caused by reactive halogen species, such as hypochlorous acid, which is released by myeloperoxidase to kill pathogens. Hypochlorous acid can attack genomic DNA to produce 8-chloro-2′-deoxyguanosine (ClG) as a major lesion. It has been postulated that ClG promotes mutagenic replication using its syn conformer; yet, the structural basis for ClG-induced mutagenesis is un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 55 publications
(69 reference statements)
1
6
0
Order By: Relevance
“…These findings support the notion that inflammaging, the chronic, low-grade inflammation that develops with age, is a common process of normal lung aging and may contribute to susceptibility to age-related pathologies [ 24 ], including DNA lesion-induced carcinogenesis [ 25 ]. Actually, a recent published systematic review and meta-analysis provides epidemiological data on the relationship between chronic inflammation and cancer incidence including lung cancer [ 26 ].…”
Section: Discussionsupporting
confidence: 81%
“…These findings support the notion that inflammaging, the chronic, low-grade inflammation that develops with age, is a common process of normal lung aging and may contribute to susceptibility to age-related pathologies [ 24 ], including DNA lesion-induced carcinogenesis [ 25 ]. Actually, a recent published systematic review and meta-analysis provides epidemiological data on the relationship between chronic inflammation and cancer incidence including lung cancer [ 26 ].…”
Section: Discussionsupporting
confidence: 81%
“…Systematic therapy for metastatic CRC is tailored with disease-specific and patient-specific predictive markers. With the progress in the research of tumorigenic mechanism, many potential therapy targets have been found [ 22 24 ], which contributed greatly to the prognosis of CRC patients. Paralleled with the breakthroughs in surgical and allied areas, the increasing kinds and number of effective drugs for CRC has led to considerable improvements of overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…Given the complexity of the mechanism of tumor carcinogenesis, fighting cancer has been a long and arduous task for many years [45][46][47]. In the field of anticancer, especially for HCC and other types of cancers that are prone to appear due to changes in various chemical substances, inflammations and molecular markers, the carcinogenic mechanism and corresponding drug development have made gratifying progress [48][49][50]. In this study, we also aimed to explore the practical value of these angiogenic genes in clinically targeted therapy, we found through pharmacological analysis that piperlongumine was an inhibitor of EGF/EGFR.…”
Section: Agingmentioning
confidence: 99%